How can funding drive firm's performance in the in vitro diagnostics industry? - Minjoon Kim; Hyunyeong Kim; Kwangsoo Shin; Changhyeon Song (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Due to the increased need for the efficient use of public funds and the importance of private investment, there have been many studies on the effects of these factors on corporate performance. However, few studies have been conducted based on an integrated perspective. In addition, most studies have investigated cases in leading countries and have rarely studied latecomer countries. Therefore, this study investigated the step-by-step effects of government support on firm performance (innovation performance, venture capital (hereafter VC) investment, and financial performance) based on the data on in vitro diagnostic (hereafter IVD) firms in Korea. In particular, we demonstrate the sequential effects of these variables with a time lag. The results of the panel regression analysis indicate that government R&D support improved the innovation performance of IVD firms, but this increased innovation performance did not attract VC investment. Meanwhile, VC investment has a positive impact on a firm's financial performance. These findings have policy implications and suggest that government support plays a pivotal role in a company's innovation performance, and thus continuous investment is required. However, innovation performance negatively affects short-term financial performance, and thus technology commercialization should be supported.
Keywords: 650; firm's performance; government R&D support; in vitro diagnostics industry; venture capital